Effects of rooting media, indolbutyric acid and fertilization on the rooting of rose (Rosa sp. 'Dalas') leafy cuttings - Pivetta, K. F L [UNESP]; Martins, A. G. [UNESP]; Ruffini, F. K. [UNESP]; Ledra, L. R. [UNESP] (My University, 1999)
The objectives of this study were to evaluate the effects of rooting media (vermiculite, carbonized rice bark, fenolic spume and sand), presence of IBA (indole-3-butyric acid) and presence of fertilization during the rooting of rose (Rosa sp.) leafy cuttings, Dalas cultivar. This investigation was carried out in Jaboticabal (Sao Paulo State - Brazil) during the period of March to April 1997. The experimental design was a randomized block in a factorial arrangement. It consisted of 16 treatments (the 4 rooting media combined with IBA concentrated solutions - 0 and 1.000 ppm and fertilizer - 0 and commercial product with macro and micronutrients, applied weekly) with 3 replicates. The evaluations were 30 days after cuttings showed that the best rooting percentage occurs in sand (98%), followed by vermiculite (90%) and fenolic spume (87%) and cuttings treated with IBA (95%), while the fertilization showed no promoting effects. The number of cuttings roots wasn't affected with rooting media or DBA treatment, while the fertilization showed effective.
Keywords: Auxin; Mist